2018
DOI: 10.1093/femsec/fiy052
|View full text |Cite
|
Sign up to set email alerts
|

The human clone ST22 SCCmec IV methicillin-resistant Staphylococcus aureus isolated from swine herds and wild primates in Nepal: is man the common source?

Abstract: Swine nasal samples [n = 282] were collected from 12 randomly selected farms around Kathmandu, Nepal, from healthy animals. In addition, wild monkey (Macaca mulatta) saliva samples [n = 59] were collected near temples areas in Kathmandu using a non-invasive sampling technique. All samples were processed for MRSA using standardized selective media and conventional biochemical tests. MRSA verification was done and isolates characterized by SCCmec, multilocus sequence typing, whole genome sequencing [WGS] and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 42 publications
3
45
1
Order By: Relevance
“…A total of 120 environmental samples were collected from 6 shrine areas of Kathmandu. e screening of environmental samples revealed that the carriage rate of S. aureus was 17.5% and of MRSA 19%, comparatively higher than the study conducted near temples areas in Kathmandu [23], where 59 saliva samples were collected from wild monkeys (Macaca mulatta), among which 6.8% macaques MRSA were isolated, with 3 ST22 SCCmec type IV and one ST239 type III; this being the first isolation of MRSA ST22 SCCmec IV from primates. A study conducted by Mbogori et al in Nairobi County from 306 samples of toilet and classroom door handles collected using sterile swabs reported the prevalence of S. aureus as 20% and 15% as MRSA positive [25]; a slightly high MRSA rate was observed in our study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A total of 120 environmental samples were collected from 6 shrine areas of Kathmandu. e screening of environmental samples revealed that the carriage rate of S. aureus was 17.5% and of MRSA 19%, comparatively higher than the study conducted near temples areas in Kathmandu [23], where 59 saliva samples were collected from wild monkeys (Macaca mulatta), among which 6.8% macaques MRSA were isolated, with 3 ST22 SCCmec type IV and one ST239 type III; this being the first isolation of MRSA ST22 SCCmec IV from primates. A study conducted by Mbogori et al in Nairobi County from 306 samples of toilet and classroom door handles collected using sterile swabs reported the prevalence of S. aureus as 20% and 15% as MRSA positive [25]; a slightly high MRSA rate was observed in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Such close contact forms the basis for the transmission of infections, including MRSA. It is known that captured primates can acquire tuberculosis and MRSA from their human caregivers, but it is unclear in what conditions wild free-ranging primates both provide and receive pathogenic bacteria from human interaction [23]. Most of the studies done till today are confined in the hospital settings because of which other areas like CA-MRSA are in shadow.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of S. aureus to acquire antibiotic resistances along with its zoonotic potential highlights the importance of studying this microorganism in other contexts, such as in free-living animals. Studies have detected and characterized S. aureus in different wild animals, such as, among others, in hares, deer, foxes, mice, mountain goats, kangaroos, hedgehogs, bears, wild boars, beavers, squirrels, shrews, bats, minks, raccoons, seals, apes, as well as in different species of birds [121][122][123][124][125][126][127][128][129][130].…”
Section: S Aureus and Mrsa In Wild Animalsmentioning
confidence: 99%
“…The t13638 was identified as the main spa type of the isolates ( n = 17/38, 44.7%) and it appeared to be a non‐human primate genotype, which was genetically close related to t189 of human origins. Interestingly, the spa type t13638 was previously reported in S. aureus isolates from cynomolgus macaques in the United States Primate Center (Roberts, Feßler, et al, ; Roberts, Joshi, et al, ), whereas spa type t189 has been found to be associated with human infections in hospitals in China (Song et al, ; Wang et al, ). In addition, the spa type t189 from this study is closely related to hospital‐associated S. aureus t002, which is frequently observed in hospital (Kates et al, ; Li et al, ; Nakao et al, ).…”
Section: Resultsmentioning
confidence: 93%